Descriptions of three new species of Uranotaenia (Pseudoficalbia) Diptera: Culicidae) from India - Natarajan, R.; Rajavel, A. R.; Jambulingam, P. (Zootaxa, 2017)
Female and male adults, male genitalia, pupa and larva of Uranotaenia (Pseudoficalbia) maikalensis, Ur. (Pfc.) dandakaranyensis and Ur. (Pfc.) satpuraensis, three new mosquito species, are described from India.